A Modified Rhomboid Flap for Medial Canthal Reconstruction. Issue 1 (27th January 2022) - Tasch, Christoph; Pattiss, Alexander; Lanthaler, Monika; Pierer, Gerhard
Abstract : Background: The reconstruction of medial canthal defects is often challenging in achieving continuity of color and texture, obtaining adequate tissue for large defects, and the reproduction of natural external appearance with inconspicuous scars. We describe a technique for reconstruction of the medial canthal area, using a modified rhomboid flap. Methods: The technique is based on the use of a modified rhomboid flap for medial canthal defects—superiorly based on the root of the nose for defects mostly above the medial canthal tendon, inferiorly based on the cheek for defects mostly below the medial canthal tendon, and in cases of large defects, using a combination of the two flaps. We present a case series of five patients successfully reconstructed with the mentioned technique after resection of medial canthal basal cell carcinoma. Results: Of the five patients with a mean age of 76.2 years (range 62–84 years), reconstruction was performed in three patients with a superiorly based rhomboid flap, in one patient with an inferiorly based rhomboid flap, and in another patient with a large defect using a combination of the two flaps. Mean follow-up was 374.4 days (range 30–1247 days). All patients achieved a complete primary closure with no further surgery and satisfactory cosmetic and functional results. Conclusion: The modified rhomboid flap is a simple and reliable technique for all defects of the medial canthal area.